1997
DOI: 10.1002/j.1552-4604.1997.tb04269.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Gender on Azimilide Pharmacokinetics After a Single Oral Dose of Azimilide Dihydrochloride

Abstract: Azimilide is a new class III antiarrhythmic drug that blocks K+ channels. To determine the effects of age and gender on azimilide pharmacokinetics, a single 150-mg oral dose was administered to 66 healthy volunteers in a 3 x 2 factorial design (age groups of 18-40, 41-64, and > or = 65 years). Blood and urine were analyzed for azimilide and metabolites. The single dose was well-tolerated. Azimilide was 94% plasma protein-bound, and binding was not affected by age or gender. Age does not affect azimilide pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…Azimilide pharmacokinetic parameters obtained in this study are consistent with those previously reported [2,3]. Azimilide is a low clearance drug [3] exhibiting extensive tissue distribution and these characteristics lead to a relatively long-terminal exponential half-life, which in this study was approximately 80 h. As in previous studies [2,3], renal clearance comprises a small percent of oral clearance (approximately 9%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Azimilide pharmacokinetic parameters obtained in this study are consistent with those previously reported [2,3]. Azimilide is a low clearance drug [3] exhibiting extensive tissue distribution and these characteristics lead to a relatively long-terminal exponential half-life, which in this study was approximately 80 h. As in previous studies [2,3], renal clearance comprises a small percent of oral clearance (approximately 9%).…”
Section: Discussionsupporting
confidence: 91%
“…assay with u.v. absorbance detection (340 nm) was used to determine azimilide concentrations in blood and urine [2]. Whole blood cells were lysed by successive freezing and warming.…”
Section: Bioanalytical Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples (sodium heparin anticoagulated) were obtained prior to and at 0.5, 1, 2, 4, 5, 6, 7 (also used for plasma protein binding), 8,10,12, and 24 h and 2, 3, 4, 5, 6, 7, 8, 9, 10, 13, 16, 19, and 22 days post-dose. Additional blood samples were also collected at 25 and 28 days after dosing in hepatically impaired subjects.…”
Section: Methodsmentioning
confidence: 99%
“…2 Following intravenous administration, azimilide pharmacokinetic parameters include: total clearance ¼ 0.136 L/h/kg; renal clearance (CL r ) ¼ 0.013 L/h/kg; steady-state volume of distribution ¼ 12.9 L/kg; and a terminal exponential halflife ¼ 71.4 h. Azimilide plasma protein binding is about 94%, 3 is concentration independent over the range observed clinically and is predominately bound to albumin, with minor binding to alpha 1 acid glycoprotein. 4,5 These parameters indicate that azimilide has a low extraction ratio (low capacity clearance) with a steady-state volume of distribution consistent with extensive tissue distribution.…”
Section: Introductionmentioning
confidence: 99%